ANALISIS PERBANDINGAN TINGKAT KESEHATAN PT. BANK KALBAR, PT.BANK JATIM, DAN PT. BANK DKIDENGAN MENGGUNAKAN METODE CAMELS TAHUN 2011-2015 - B31111008, Mukti Wahyuni (Jurnal Manajemen Update, 2016)
Banking sector, particularly bank, as part of a finance system takes an important role as intermediation institution for sectors who involved in an economyc matters, therefore bank health level must be given the serious attention because it involved the significance of many parties that bound the owner, government, as well as the society who use the bank services. The purpose of this research is to find and analyze the condition of health level the Regional Development Bank of West Kalimantan, Regional Development Bank of East Java, Regional Development Bank of DKI Jakarta using CAMELS Methods. Types of this research is descriptive comparative. Methods of data collection in this research is using a secondary data which was obtained indirectly but it was obtained by official sites. This secondary data was obtained in the form of routine financial reports issued by the Bank. The results show that PT. Bank Kalbar and PT. Bank Jatim on aspects Capital (CAR), Asset (NPL), Management (NPM), Earning (ROA and ROA), Liquidity (LDR), and Sensitivity to Market Risk (IER) from 2011-2015 categorized healthy, while PT. Bank DKI in LDR ratio in 2013 did not indicates a good condition and in 2015 on aspects of NPLs, ROA and IER also did not indicate a good condition. Keywords : CAMELS ratio, Bank Health